Analysis of Determinants Affecting Profitability in Pertamina Papua Field - Muhamad Husein; Jagat Prirayani (Green Publisher Indonesia, 2026)
This study investigates profitability determinants in marginal oil field operations, addressing whether profitability is primarily driven by management-controllable internal factors or market-driven external conditions. Using 60 monthly observations from January 2019 to December 2023 from the Pertamina Papua Field, we employ a three-model regression framework systematically separating internal operational factors (Model 1), external market conditions (Model 2), and combined effects (Model 3). Empirical findings establish that internal management-controllable factors explain 89.12% of profitability variance (R² = 0.8912, F = 72.34, p < 0.001), while external market-driven factors explain 52.34% variance (R² = 0.5234, F = 31.23, p < 0.001). The 37-percentage point explanatory power gap quantifies internal factor dominance. Lifting cost emerges as the dominant determinant with coefficient -9.12 (p < 0.001), indicating each dollar-per-barrel increase reduces Return on Assets by 9.12 percentage points. Oil price demonstrates positive coefficient +1.34 (p < 0.001), yet comparison reveals cost reduction provides 6.8 times greater profitability impact than equivalent price increases. The combined model (R² = 0.9600, F = 89.45, p < 0.001) validates a coefficient ratio of 7.3:1 between lifting cost and oil price effects, establishing that cost management is 7.3 times more powerful than price movements in determining profitability. Incremental R-squared analysis demonstrates internal factors contribute 9.4 times more explanatory power than external factors. Strategic recommendations suggest allocating 80-85% of transformation resources toward internal operational improvements and 15-20% toward external risk management, projecting Return on Assets transformation from -20.25% to +35-55% within 24 months.